Modelling of household wastewater pollutants in Kuching, Sarawak - Siew, Tuck Fatt (Universiti Malaysia Sarawak (UNIMAS), 2002)
The objective of this study as to determine the quantity and quality of household wastcsyater and thus develop pollutant loading models as a function of socio-economic variables. The study was carried out at six residential areas in Kuching. namely RPR Ratu Kawa, Taman Malihah, Tahuan Java, Taman Satria Jaya, Village Grove Condominium. and De Summit Condominium. The residential areas were categorised into low-, middle- and high-income groups. Floe rates determination showed that the loss-income residential areas, RPR Ratu Kasa and Tanrm Malihah, discharged large quantity of wastewater throughout the day, 49.9 I/cap/day and 52.4 I cap, 'da) respectively, whilst "Taman Satria Java and Dc Summit Condominium had the lowest floe, 40.2 I, cap-day and 34.5 I/cap/day respectively. Four water quality parameters were selected for the modelling study i. e. RODc, phosphate, nitrate, and Iseherichca cols. The results showed that the BOD, (21.94 mg/l) and nitrate (0.16 mg/I) concentrations were relatively high in De Summit Condominium which is a high-income residential area. On the other hand, RPR Ratu Ka%ka and Taman Malihah contributed to the greatest amounts of phosphate (10 12 mg/I) due to higher level of household activities especially cashing %%hich also contributed to higher flow compared to other residential areas. Tabuan Jaya. RPR Ratu Kawa, and Taman Malihah discharged high E. co/i loads of4.8I x 109 CFU/cap/day, 3.33 x 109 C'H 'cap/day and 3.35 x 10" CFIJ/cap/day respectively, into the sewerage systems. This is most likely due to the fact that the septic tanks had never been desludgcd although the premises had been occupied for more than 10 year. Six models of pollutant loadings were dc%cloped as a function of socio-economic variables. 1 hose models included 1«01)s concentration, /: co/i count,, phosphate load and nitrate load as a function of average monthly total household income as well as phosphate load and E co/i counts as a function of per capita water consumption. the models wcre tested with field data. The testing of the models showed that the amount of pollutant discharged were dependent on local conditions as well as the behaviour of the individual household that affected the lifestyle consistency. These are the most likely causes in the variations of quantity and quality of pollutant loadings. Finally, an example of model application was presented to predict the pollutant loading in Kuching. The estimated F. co/i loading from residential areas was high. The findings through modelling of pollutant loading are able to assist in the design of %yastewater collection, treatment and disposal systems.